(untitled) (Ictus, 2023)
Cryptogenic stroke represents a heterogenous but clinically important collection of stroke etiologies for which our understanding continues to grow. Here, we review our current knowledge and most recent recommendations on secondary prevention for common causes of cryptogenic stroke including paroxysmal atrial fibrillation, atrial cardiopathy, patent foramen ovale, and substenotic atherosclerotic disease as well as the under-recognized mechanisms of occult malignancy, heart failure, and, most recently, infection with severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2). The results from recent observational studies and randomized clinical trials have provided greater insight into the causal relationship and attributable risk of these suspected etiologies and have identified potential strategies to reduce the rates of recurrence. However, further clinical trials are needed to confirm the benefits of specific stroke prevention strategies, including the patient populations most likely to benefit from anticoagulation. There is ongoing research aimed at both reducing the proportion of ischemic strokes classified as cryptogenic and resolving much of the clinical equipoise that still exists. The results of these studies have the potential to provide us with a better understanding of these occult mechanisms and allow for more targeted interventions.